Peningkatan Kualitas Air Hasil Paparan Larvasida Hayati Kulit Kayu Gemor (Nothaphoebe coriacea K.) - Pranatasari Dyah Susanti; Wawan Halwany (Jurnal Ilmu Pertanian Indonesia, 2019)
Biolarvacide derived from local plant extract can be used as a vector breaker for diseases caused by mosquitoes. One of plants used as biolarvacide was gemor bark. The use of gemor bark as a biolarvacide had caused a high mortality for mosquitoes, but had lowered the quality of water exposed by this larvacide. The objective of this research was to study a method to improve water quality exposed to biolarvacide of gemor bark extract. This research used experimental methods with 5 treatments and 3 replications, while the research design was using a completely randomized design. The treatment used in this research was purification using flannel fabric, cotton fabric; adding PAC (Poly Aluminium Chloride) 10 mL, PAC 30 mL, and PAC 50 mL. The dose of biolarvacide extract used was 1600 ppm. Parameters measure were pH and turbidity. Research results showed that averages pH in G1; G2; G3; G4; and G5 were 5.67; 5.67; 7.27; 7.12; and 7.02, respectively. While the turbidities in G1; G2; G3; G4; and G5 were 471 NTU; 414.33 NTU; 8.67 NTU; 2.82 NTU; and 1.22 NTU, respectively. Based on Regulation of Health Ministery of Indonesia No. 32 year 2017 about Quality Standard of Environmental Health and Water Health Requirements for Hygiene Sanitation, Swimming Pool, Solus Per Aqua, and Public Bath, and Further Analyses, then G4 treatment can be used as alternative treatment for purification of water exposed by gemor bark larvacide.